Heteropoly acid encapsulated SBA-15/TiO(2) nanocomposites and their unusual performance in acid-catalysed organic transformations - Sawant, Dhanashri P.; Justus, Josena; Balasubramanian, Veerappan V.; Ariga, Katsuhiko; Srinivasu, Pavuluri; Velmathi, Sivan; Halligudi, Shivappa B.; Vinu, Ajayan (Chemistry-A European Journal, 2008)
The preparation of SBA-15/TiO(2) nanocomposites with different loadings of Keggin-type 12-tungsto-phosphoric acid (TPA) nanocrystals in their mesochannels through a simple and effective vacuum impregnation method is reported for the first time. The catalysts have been characterised by various sophisticated techniques, including XRD, HRSEM, and TEM. It has been found that the acidity and the textural parameters of the nanocomposites can be controlled by simply changing the loadings of TPA and TiO(2) or the calcination temperature. TPA and TiO(2) loadings of 15 and 22.4 wt %, respectively, and a calcination temperature of 1123 K have proved to be optimal for obtaining mesoporous nanocomposite materials with the highest acidity. Moreover, the activities of these catalysts in promoting hydroamination as well as Mannich and Claisen rearrangement reactions have been extensively investigated. The results show that the amount of TPA has a great influence on the activity of the nanocomposites in all of the reactions studied. The effects of other reaction parameters, such as temperature and reaction time, on the conversion and product selectivity have also been studied in detail. A kinetic analysis of the formation of the products under various reaction conditions is presented. It has been found that the activity of the nanocomposite composed of 15 wt % TPA deposited on 22.4 wt of TiO(2) on SBA-15 in promoting the studied reaction is remarkably higher than the catalytic activities shown by pure TPA, TiO(2)-loaded SBA-15, or TPA-loaded SBA-15. The results obtained have indicated that the acidity and the structural control of the nanocomposite materials are highly critical for obtaining excellent catalytic activity, and the presented highly acidic nanocomposites are considered to show great potential for use as catalysts in promoting many acid-catalysed organic transformations.
Keywords: Bronsted acids; mesoporous materials; nanoreactors; nanotechnology; supported catalysts

Novel three dimensional cubic Fm3m mesoporous aluminosilicates with tailored cage type pore structure and high aluminum content - Srinivasu, Pavuluri; Alam, Sher; Balasubramanian, Veerappan V.; Velmathi, Sivan; Sawant, Dhanashri P.; Boehlmann, Winfred; Mirajkar, Subhash P.; Ariga, Katsuhiko; Halligudi, Shivappa B.; Vinu, Ajayan (Advanced Functional Materials, 2008)
Novel three dimensional cubic Fm3m mesoporous aluminosilicates (AIKIT-5) with very high structural order and unprecedented loadings of Al in the silica framework have been successfully prepared for the first time by using non ionic surfactant as a template in a highly acidic medium. The obtained materials have been unambiguously characterized in detail by several sophisticated techniques such as XRD, N, adsorption, HRTEM, HRSEM, EDS, elemental mapping, Al-27 MAS NMR, and NH3-TPD. We also demonstrate that the nature, and the amount of Al incorporation in the silica framework can easily be controlled by simply varying the n(H2O)/n(HCl) and the n(Si)/n(Al), ratios, and the Al sources in the synthesis gel. Among the Al sources examined, the Al isopropoxide (AiPr) is superior over other Al sources. Al-27 MAS NMR results reveal that the amount of tetrahedral Al in the framework can be controlled by simply adjusting the nSi/nAl ratio in the synthesis gel, which increases with increasing the Al incorporation. One of the interesting findings in the work is the increase of the specific surface area, specific pore volume and the pore diameter of AIKIT-5 with increasing the Al incorporation in the silica framework (up to n(Si)/n(Al), ratio of 10) while retaining the well-ordered three dimensional cage type porous structure, and the mechanism for the unusual behavior has been discussed in detail. Finally, the acidity and the catalytic activity in the acetylation of veratrole of the AIKIT-5 catalysts have been studied and the results have been compared with the several zeolites catalysts. Among the catalysts examined, AIKIT-5(10) is found to be superior over the zeolites catalysts such as mordenite, zeolite H-Y, zeolite H-beta, and ZSM-5.